Assessment of work environment factors influencing job satisfaction among mortuary staff in Nairobi City County, Kenya - Ogira, Dosila A.; Warutere, Peterson N.; Yitambe, Andre (International Journal Of Community Medicine And Public Health, 2023)
Background: Job satisfaction has been widely studied as a key factor that influences efficiency and effectiveness among healthcare workforces. However, one notable category that has been largely overlooked by researchers are the mortuary staff in part because of the stigma surrounded in the topic of death leading to them working in deplorable work environments. This study sought to address this gap by examining work environment factors influencing job satisfaction among mortuary staff in selected public and private mortuaries in Nairobi City County, Kenya. Methods: Cross sectional study design, adopting qualitative and quantitative data collection was used in this study. A sample size of 193 respondents were selected from public and private mortuaries. Key Informant interviews were used to provide additional qualitative data. Results: The study revealed that the overall satisfaction level was 44.7%. Chi-square analysis revealed significant relationship between; marital status (p=0.033) and solidarity among employees in the department (p=0.024). However, other factors such as provision of the right tools and equipment (p=0.061), appropriateness of daily working hours (p=0.265) and level of staffing (p=0.264), were not statistically significant in this study. Conclusions: The study revealed a suboptimal job satisfaction level among mortuary staff in Nairobi County. This research calls for a better understanding of the dynamics of job satisfaction among mortuary staff by facility administrators as well as policy makers. Such information is integral to future policy development and decisions about appropriate strategies for intervention.